Consumer acceptance towards night zoo at Zoo Melaka: An analysis on marketing mix strategies / Noorasliaomie Padlan - Padlan, Noorasliaomie (Faculty of Business and Management, 2008)
The purpose of this research is to measure the effectiveness of the marketing mix strategy towards Night Zoo at Zoo Melaka by identifying the level of consumer acceptance towards the marketing mix strategy. The dependent variable for this research is consumer acceptance and the component of marketing mix, which consists of product, price, promotion and place, represents the independent variables. The research is conducted at Zoo Melaka where 70 questionnaires have been distributed. The questionnaires was distributed during the operational hours of Night Zoo. Based on the study, the researcher finds that consumer moderately accepts Night Zoo at Zoo Melaka. Furthermore, among the four components of marketing mix, place is the most influential factors that contribute to the consumer acceptance towards Night Zoo at Zoo Melaka. While, in term of relationship, all of the four components in marketing mix have significant relationship with consumer acceptance. Through the findings of the research, it can be concluded that all of the four components in marketing mix done by Zoo Melaka for Night Zoo is moderately effective.